Civilian Applications of Atomic Energy - Cockcroft, John (Defence Science Journal, 2013)
Sir John Cockcroft showed a film illustrating the handling of radioactive materials at Harwell. He concluded the lecture by saying that great care had to be taken in disposing of the radioactive affluent. Before discharging it into the Thames which is the source of London's water supply they had to be quite certain that the radioactivity level in the water was very low.